CHARACTERISTICS OF BOTH PROTEIN CONCENTRATES CUNANG FISH (Muraenesox talabon) USING SOLVENTS ETHANOL WITH A DIFFERENT TIME - Tia Novita Laili; Edison Edison; Rahman Karnila (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTFish protein concentrate is a starchy product which is produced by removing fat and water. This study aims to determine the effect of different times on the characteristics of the protein concentrate of cunang fish (Muraenasox talabon) using ethanol as a solvent. The main ingredients used are cunang fish and 95% ethanol solvent. The research stages included (1) extraction using ethanol with a ratio of 1: 3 with different times of 12 hours, 18 hours and 24 hours, (2) determining the nutritional content of the protein concentrate of cunang fish, water absorption and dissolved protein. The results showed that the average yield of 12 hours was 29.06%, 18 hours 29.35% and 24 hours was 29.85%. Nutritional content of fatty fish meat 31.62% (bk), 65.24% protein (bk), ash 2.96% (bk), water 71.97% (bb), 0.18% carbohydrates (bk). Fish protein concentrate which had a fat amount of water and was weak was found at 24 hours of extraction time, namely 3.20% fat (bk) and 78.73% protein (bk). This product has functional properties, namely water absorption capacity of 12 hours 6.64g/mL, 18 hours 6.73 g/mL, 24 hours 6.44g/mL, and dissolved protein 12 hours 0.18%, 18 hours 0.24%, 24 hours 0.16%. Keyword: Cunang Fish,Fish Protein Concentrate, Ethanol